MALDI-TOF mass spectrometric protein profiling of microvesicles produced by the NK-92 natural killer cell line - A. V. Korenevsky; A. D. Shcherbitskaia; M. E. Berezkina; K. L. Markova; E. P. Alexandrova; O. A. Balabas; S. A. Selkov; D. I. Sokolov (Медицинская иммунология)
Extracellular vesicles that are shed from the plasma membrane contain a wide range of molecules, among  which  are proteins, lipids, nucleic  acids,  and sugars. The cytotoxic proteins of natural killer cells play a key role in the implementation of their cytolytic  functions. One of the important steps in understanding the distant  communication of cells is the determination of the proteome of microvesicles. This study was aimed at the protein profiling of the microvesicles produced by the NK-92 natural killer cell line. 986 proteins with a variety of functions were identified in the lysate of microvesicles using the MALDI-TOF mass spectrometric analysis.  With automated methods of functional analysis  applied, it has been  shown  that  the  largest  protein groups  are  hypothetical proteins, proteins with  unknown functions, and  domains. The  most  representative groups  are  also  comprised by  transcription  regulators; intracellular  signaling  proteins; RNA  translation, transcription, processing, and utilization regulators; receptors; protein processing  and proteolysis regulators; amino acid metabolism enzymes, as well as transport proteins and transport regulators. Minor functional groups are represented by vitamins and mineral metabolism enzymes, membrane and microdomain-forming proteins, hormones, hemostatic regulators, regulators of sensory  systems,  specific  mitochondrial and  Golgi  apparatus proteins, and extracellular signaling proteins. An intermediate position is occupied by various functional groups, including cytoskeleton and motor proteins; proteins of centrioles; ion channels and their regulators; proteins of the ubiquitin-proteasome pathway  of protein degradation; lipid,  steroid, and fatty acid metabolism enzymes; nucleic  acid  base and  carbohydrate metabolism enzymes, as well as energy  metabolism enzymes  and  other proteins involved  in intermediate metabolism; proteins of the immune response  and  inflammation; antigens and histocompatibility proteins; cytokines and growth factors; regulators of apoptosis, autophagy, endocytosis, and  exocytosis;  regulators of the  cell cycle and  division;  regulators of proliferation, cell differentiation, and morphogenesis; regulators of cell adhesion and  matrix  metabolism; nuclear transport proteins; transposition proteins; DNA  replication and  repair  proteins, as well as inactive  proteins. The  data  obtained expand  the existing knowledge of the distant  communication of cells and indicate new mechanisms of interaction between natural killer and target cells.